Crossover rate between homologous chromosomes and interference are regulated by the addition of specific unpaired chromosomes in Brassica. Issue 2 (1st October 2013) - Suay, Loreto; Zhang, Deshuang; Eber, Frédérique; Jouy, Hélène; Lodé, Maryse; Huteau, Virginie; Coriton, Olivier; Szadkowski, Emmanuel; Leflon, Martine; Martin, Olivier C.; Falque, Matthieu; Jenczewski, Eric; et al.
Summary: Recombination is a major mechanism generating genetic diversity, but the control of the crossover rate remains a key question. In Brassica napus (AACC, 2 n  = 38), we can increase the homologous recombination between A genomes in AAC hybrids. Hypotheses for this effect include the number of C univalent chromosomes, the ratio between univalents and bivalents and, finally, which of the chromosomes are univalents. To test these hypotheses, we produced AA hybrids with zero, one, three, six or nine additional C chromosomes and four different hybrids carrying 2 n  = 32 and 2 n  = 35 chromosomes. The genetic map lengths for each hybrid were established to compare their recombination rates. The rates were 1.4 and 2.7 times higher in the hybrids having C6 or C9 alone than in the control (0C). This enhancement reached 3.1 and 4.1 times in hybrids carrying six and nine C chromosomes, and it was also higher for each pair of hybrids carrying 2 n  = 32 or 2 n  = 35 chromosomes, with a dependence on which chromosomes remained as univalents. We have shown, for the first time, that the presence of one chromosome, C9, affects significantly the recombination rate and reduces crossover interference. This result will have fundamental implications on the regulation of crossover frequency.